The Influence of Jazz in 20th-Century Classical Clarinet Music: A performance-based investigation of Copland's Clarinet Concerto and Bernstein's Clarinet Sonata - Rotevatn, Marie (College of Music, 2024)
Playing classical compositions containing stylistic elements of jazz can be a challenge for a classically trained clarinettist. This study explored how to play such compositions by investigating, learning, and performing Concerto for Clarinet and String Orchestra (with Harp and Piano) by Aaron Copland and Sonata for Clarinet and Piano by Leonard Bernstein. Considering the historical context and exploring the works practically, the stylistic influence of jazz was unpacked through practice-based research and performance practice. Upon analysis, it was found that both compositions incorporate jazz elements such as rhythm and timbre. Further, an influence of jazz in terms of context was discovered. Bernstein and Copland's other works and Benny Goodman's fame as “The King of Swing” somewhat affect the perception of jazz-influence. The original recordings of the two compositions revealed how both works were played in the classical idiom and with close attention to the markings in the sheet music. However, newer recordings of the two compositions incorporate stylistic elements of jazz that were not present in the original recordings.